Socio-demographic and other risk factors associated with HBV potential infectivity among Hepatitis B Surface Antigen Negative blood donors - Busari EBenezer Olusogo; Ojo Omotola Toyin; Aken'Ova Yetunde Adebisi (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2018)
Background: There have been cases of post-transfusion hepatitis in spite of transfusion of hepatitis B surface antigen negative blood unit. Objective: To determine the socio-demographic and risk factors associated with positivity of anti-HBc among Hepatitis B surface antigen negative blood donors. Methods: A cross-sectional study was carried out among 490 HBsAg negative blood donors. The participants were tested for anti-HBc using ELISA kits. A structured questionnaire was used to obtain socio-demographic data and other possible risk factors. Results: The mean age of the participants was 32.5 ± 9.5 years with male predominance of 462 (94.3%) while 375 (76.5%) were first time donors. Of the 490 HBsAg negative blood donors, 89 (18.2%) were positive for anti-HBc. The highest prevalence of anti-HBc occurred in the 26-34 years age group. Independent risk factors associated with the presence of anti-HBc included age (p = 0.049), marital status (p = 0.003), dental and surgical procedure (p<0.001), traditional practices such as tattoo, body piercing and scarification (p<0.001) and previous blood transfusion (p = 0.016). Conclusion: Age, marital status, traditional and cultural practices like scarifications, tattoo and body piercing and history of blood transfusion were risk factors associated with HBV infection despite HBsAg negativity.